Impacts of microplastics on agroecosystem multifunctionality: From plant production to soil microbial diversity and functions - Zhenxiu Liu; Yali Liu; Zifang Zhou; Yangbeijia Liu; Shiqiang Ge; Chang Shen; Ziqiang Liu; Jianwu Wang (Environmental Chemistry and Ecotoxicology)
Ubiquitous microplastics (MPs) in agricultural practices garner global concerns, with potential implications for agroecosystem functions and services. The comprehensive evaluation of MPs impacts in agroecosystem is imperative and crucial for understanding their ecological risks. Herein, microcosm experiments were performed to elucidate the changes of plant production, soil quality, microbial community diversity, enzymes involved in carbon (C), nitrogen (N) and phosphorus (P) cycling, and overall ecosystem multifunctionality (EMF) under the addition (0.1 %, 1 %, and 5 %; w/w) of polyethylene (PE), polypropylene (PP), and polystyrene (PS) MPs in maize-soil systems. The results showed that all types of MPs negatively influenced maize growth, with the most significant changes observed for PP MPs. PE MPs decreased soluble sugars and free amino acids content. High-concentration (5 %) PP and PS inhibited the activity of catalase involved in antioxidant defense mechanisms. All types of MPs increased soil carbon storage, while decreased the phosphorus availability. Low concentration (1 %) of all types of MPs promoted bacterial α-diversity while exerted negligible effect on fungal α-diversity. All types of MPs tended to increase the bacterial and fungal complexity. Overall, low-concentration PE (0.1 % and 1 %) and PS (0.1 %) improved EMF due to the enhanced bacterial α-diversity and C- or N-related enzymes activities, and altered microbial community structure. However, the promoting effects on EMF disappeared with increasing the dose of MPs pollution. These results highlight the potentially detrimental effects of MPs on agroecosystems, thus development and implement of scalable solutions controlling soil MPs pollution become increasingly imperative in agricultural production.